Analisis Penggunaan Drone untuk Meningkatkan Respons Cepat dalam Penanganan Kecelakaan Pesawat di Area Terpencil - Ahmad Fiqri; Alfan Hugo; Nawang Kalbuana (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
The use of drones in responding to aircraft accidents in remote areas is an important innovation to improve response and efficiency in emergency situations. The purpose of this study is to explore the optimization of drone use in this context using qualitative research methods and a descriptive approach with interviews, observations, and document analysis. The research showed that drones have a variety of benefits, among others: These include fast and accurate monitoring of accident sites, detailed real-time data collection for situation assessment, and the ability to provide medical assistance and rescue equipment quickly and efficiently. In addition, drones can reach areas that are difficult for traditional rescue teams to access, thereby reducing the risk to rescue workers and speeding up the search for victims. However, some obstacles have also emerged, including limited communication infrastructure that can hinder drone operations in remote areas and difficulties in coordinating drone operators with rescue teams on the ground. Other technical challenges include the limited battery life of drones, extreme weather conditions that can affect drone performance, and the need for drone operators to use their drones. effectively and safely. Future research is suggested to focus on evaluating the effectiveness of drone use in various emergency situations, further development of drone technology, and analysis of the regulatory and legal aspects of drone use. The aim of this initiative is to ensure the optimal and safe use of drones in future rescue operations, especially in remote areas that are difficult to reach by traditional methods. Cooperation between the government, technology service providers and rescue teams is also essential to overcome barriers and maximize the potential of drone use.